Biomarkers of human papillomavirus (HPV)-driven head and neck cancer in Latin America and Europe study: Study design and HPV DNA/p16(INK4a) status - Sichero, L (2022)
Background: Human papillomavirus (HPV)-driven head/neck squamous cell carcinomas (HNSCC) prevalence varies globally. We evaluated HPV DNA and p16INK4a in formalin fixed paraffin embedded (FFPE) HNSCC from Argentina, Brazil, Colombia, and Peru. Methods: HPV was genotyped by PCR-hybridization. All HPV DNA positive and some HPV DNA negative cases underwent p16INK4a immunohistochemistry. Results: HPV DNA was detected in 32.8%, 11.1%, and 17.8% of oropharyngeal (OPC), oral cavity (OCC) and laryngeal (LC) cancers, respectively. OPC HPV prevalence was higher in Colombia (94.7%), and Argentina (42.6%) compared to Brazil (10.6%) and Peru (0.0%). HPV-16 was the most detected. Other HPVs were found in LC. Higher rates of p16INK4a positivity were observed among HPV positive OPC/OCC cases compared to LC cases. Conclusions: Our results support a role for HPV-16 in a subset of HNSCC, corroborate the heterogeneity observed in samples from different countries, and contribute additional etiological and biomarkers information in tumors of significant impact worldwide. Keywords: head and neck cancer; human papillomavirus; multinational study; prevalence; risk factors.